Metal–Insulator–Semiconductor Coaxial Microfibers Based on Self‐Organization of Organic Semiconductor:Polymer Blend for Weavable, Fibriform Organic Field‐Effect Transistors. (19th February 2016) - Kim, Hae Min; Kang, Hyun Wook; Hwang, Do Kyung; Lim, Ho Sun; Ju, Byeong‐Kwon; Lim, Jung Ah
Abstract : With the increasing importance of electronic textiles as an ideal platform for wearable electronic devices, requirements for the development of functional electronic fibers with multilayered structures are increasing. In this paper, metal–polymer insulator–organic semiconductor (MIS) coaxial microfibers using the self‐organization of organic semiconductor:insulating polymer blends for weavable, fibriform organic field‐effect transistors (FETs) are demonstrated. A holistic process for MIS coaxial microfiber fabrication, including surface modification of gold microfiber thin‐film coating on the microfiber using a die‐coating system, and the self‐organization of organic semiconductor–insulator polymer blend is presented. Vertical phase‐separation of the organic semiconductor:insulating polymer blend film wrapping the metal microfibers provides a coaxial bilayer structure of gate dielectric (inside) and organic semiconductor (outside) with intimate interfacial contact. It is determined that the fibriform FETs based on MIS coaxial microfiber exhibit good charge carrier mobilities that approach the values of typical devices with planar substrate. It additionally exhibits electrical property uniformity over the entire fiber surface and improved bending durability. Fibriform organic FET embedded in a textile is demonstrated by weaving MIS coaxial microfibers with cotton and conducting threads, which verifies the feasibility of MIS coaxial microfiber for use in electronic textile applications. Abstract : A metal–polymer insulator–semiconductor (MIS) coaxial microfiber based on self‐organization of the organic semiconductor:insulating polymer blend is demonstrated for use in electronic textile applications. Fibriform field effect transistors based on MIS coaxial microfiber exhibit good electrical properties with bending durability. A transistor embedded in a textile is realized by weaving MIS coaxial microfibers with cotton and conducting threads.